PERAN SEKTOR BASIS DALAM PENYERAPAN TENAGA KERJA DI PROVINSI SULAWESI UTARA - Oktavianus ., Katiandagho; Gene H. M Kapantouw; Caroline B. D. Pakasi (Sam Ratulangi University, 2017)
This study aims to determine what sectors into the base sector and the role of base sectors on employment within the last 5 years in the Province of North Sulawesi study was conducted over three months starting in October 2016 until the month of December 2016 in the province of North Sulawesi. In this study, the data used is secondary data obtained from the Central Statistics Agency (BPS) of North Sulawesi Province. The data is processed using descriptive analysis and presented in tables and graphs. From the results of research show that the sector became the sector base in North Sulawesi are agriculture, forestry and fisheries, construction, and transport and communications sectors. In the agricultural sector the rate of labor absorption is much larger than the other two sectors of the base, but the growth rate of its workforce decreased when compared with other bases of both sectors. It can be seen from the average level of labor absorption per each sector of a base. At the rate of growth of gross regional domestic product (GRDP) of North Sulawesi province to the agricultural sector amounted to 21.70 percent and the rate of employment growth of 0.22 percent, the construction sector amounted to 12.71 per cent with employment growth rate of 0.44 percent, while transport and communication sector amounted to 12.59 with labor force growth rate of 2.97 percent.